PELABUHAN TERPADU MARUNDA SEBAGAI SARANA PENUNJANG RUMAH SUSUN MARUNDA DI JAKARTA DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Rizka Devianty; Widi Suroto; Amin Sumadyo (ARSITEKTURA, 2014)
Abstract: Jakarta Provincial Government initiated the concept of integrated development Marunda towers that are intended for low-income residents who live in the area of potential flooding. Location of Marunda area located in the North Coast Jakarta potentially has access to the attainment of the region using the waterway. Procurement as a water taxi transportation facilities for residents Marunda towers insufficient capacity Marunda residents who want to use the water taxi, so it requires a regional port that connects to the towers Marunda other strategic places. Integrated port Marunda an attempt to summarize all activities and support facilities for residents surrounding the towers Marunda regional ports and traditional markets. The purpose of the planning and design of the (1) How integrated port Marunda able to provide support facilities to meet the transportation needs in the form of regional ports and primary needs, (2) How to maintain the ecological balance of the environment through the grades. Integrated port Marunda required the principles of ecological design as a method to preserve the environment for the present and the future.  Keywords: Ecological Architecture, Integrated Ports, Marunda Flat.